Exploring key determinants of health literacy in type 2 diabetes patients: A cross-sectional study - Huyen, Do Thi Thu (Tạp chí Nghiên cứu Y học, 2025)
Health literacy (HL) is a critical factor in the management of type 2 diabetes mellitus (T2DM), yet many patients lack adequate understanding, leading to poor health outcomes. This study assessed HL among patients with T2DM and identified associated factors. This cross-sectional study involved 358 diabetic outpatients who completed a self-reported questionnaire, including the Health Literacy - Short Form (HL-SF12), Diabetes Self-Management Instruments (DSMI-20), and Multi-Dimensional Support Scale (MDSS). Analysis using SPSS 26.0 revealed an average HL score of 26.3 ± 5.3, with 88.9% of participants demonstrating inadequate HL. Patients under 60 years old, those with higher education, a monthly income over 5 million VND, diabetes duration of less than 5 years, non-alcohol consumers, and effective self-managers showed notably higher HL scores (p < 0.05). Four factors are likely to influence the HL, including “Age” (β = -0.23; 95% CI: -0.27, -0.19; p < 0.001), “Educational level” (β = 3.56; 95% CI: 2.49, 4.64; p < 0.001), “Income” (β = 1.25; 95% CI: 0.54, 1.96; p = 0.001), and “Self-management” (β = 0.12; 95% CI: 0.08, 0.16; p < 0.001. Recommendations include reinforcing health information sources and education programs, to enhance comprehension and self-management skills, contributing to more effective care and education strategies for T2DM patients, particularly elderly patients.